Effect of flexural strength and density properties of sugarcane bagasse reinforced unsaturated polyester composites - Ruslan Shamsuddeen; Aminu Sanusi Haruna; Ziyaulhaq Auwal Abdulkadir; Hussaini Faruq; Ansar Bilyaminu Adam; Musa Yahaya Abubakar; Mohammed Alhaji Usman (Romanian Journal of Ecology & Environmental Chemistry)
As a byproduct of sugarcane processing, bagasse offers a sustainable alternative to conventional synthetic fibers in composite materials. Due to its abundance, low weight, and favorable mechanical properties, sugarcane bagasse has recently attracted increased scientific interest as a reinforcement in plastic composites. This study investigated the effects of sugarcane bagasse (SCB) weight fraction, particle size variation, and chemical treatments on the flexural strength and density of unsaturated polyester resin (UPR) composites. To enhance the adhesion between the bagasse fibers and the polymer matrix, chemical treatments with 5% hydrogen peroxide and 10% sodium hydroxide were applied. The SCB-reinforced UPR composites were fabricated using compression molding, followed by a 5-minute curing process at 130°C and a pressure of 2.5 MPa. Flexural strength and density were then evaluated. Results showed that flexural strength increased with higher bagasse loading, attributed to improved fibber–matrix intermixing. In contrast, density decreased as fibber content increased; for instance, at 100% UPR and 25% weight of 710 µm particles, the density dropped from 1.37 g/cm³ to 0.55 g/cm³. The composite's low weight, combined with its favorable flexural strength and density characteristics, suggests its suitability for structural applications.